The Determining Role of EU in Turkey's Trade Flows: A Gravity Model Approach - Özgül Bilici; Erkan Erdil; I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2008)
This paper aims to determine the role of EU in Turkey's trade flows by using the gravity model. It also aims to test whether the Customs Union (of EU) that Turkey entered in 1996 made a deviation in Turkey's trade flows. Regional trade agreements on the one hand create new trade opportunities (trade creation effect). On the other hand, these agreements may also lead to diversion from free trade (trade diversion effect). Turkey's Customs Union agreement without becoming a member of EU provides a laboratory to researchers to test whether the agreement was significant enough to cause any deviation in Turkey's trade flow. In the first part of the study, we shortly provide some descriptive statistics related to Turkey's trade flows with EU to see whether EU has gained any weight in the flows. In the second part, we first develop a gravity model that econometrically designates the determinants of Turkey's trade flows via panel data approach. Next, we use this equation to test the importance of EU countries in Turkey's trade flow and whether the flow has been subject to a deviation after the Customs Union agreement. Our findings indicate that EU countries have always been important in Turkey's trade flow and that Customs Union has increased EU's importance marginally in determining Turkey's trade flow.
Keywords: F02; F11; F13; F14; F21; 330; Gravity model; Turkey; EU; Panel Data; Customs Union; Internationale Wirtschaftsbeziehungen; Gravitationsmodell; Zollunion; Türkei; EU-Staaten